Causal Model of Civil Servant Retention Based on Training Programs and Career Development: A Mediation Approach in Regional Bureaucratic Reform (International Journal of Economics and Management Research, 2026)
The research seeks to investigate the impact of training programs and career development on employee retention among Civil Servants (ASN) in the General Affairs Division of the Regional Secretariat of Batang Regency. Employee retention is a strategic concern that influences the continuity of public services, bureaucratic effectiveness, and efficiency in human resource management. The observed gap lies between the government’s substantial investment in training and career development initiatives and the relatively low retention rate of civil servants. This study employs a quantitative approach, with the entire population of 78 ASN included as the sample through a saturated sampling technique. The independent variables consist of training programs (relevance of training content, facilitator quality, frequency, organizational support, and transfer of learning) and career development (formal career planning, promotion opportunities, mentoring, talent management, and merit system transparency). The dependent variable is employee retention, measured through tenure intention, work engagement, job satisfaction, and turnover rate. Data analysis was conducted using JASP software, applying linear regression and classical assumption tests to examine the direct relationships among variables. The findings are expected to provide empirical evidence that training programs and career development positively and significantly affect ASN retention, while also identifying the most influential dimensions within the bureaucratic context. This study contributes to evidence-based human resource policies that strengthen organizational stability, support bureaucratic reform, and ensure sustainable public service delivery.